Early Term versus Term Delivery in the Management of Fetal Growth Restriction: A Comparison of Two Protocols - Dahlke, Joshua D.; Mendez-Figueroa, Hector; Maggio, Lindsay; Albright, Catherine M.; Chauhan, Suneet P.; Wenstrom, Katharine D. (American Journal of Perinatology, 2015)
Objective This study aims to compare two management protocols in pregnancies diagnosed with fetal growth restriction (FGR).Study Design All singleton pregnancies diagnosed and managed with FGR at our institution during two protocol periods were analyzed. The early term protocol (January 2008–February 2010) specified delivery at 370/7 weeks if antenatal testing was reassuring, but did not specify the timing of delivery if umbilical artery (UA) Doppler systolic:diastolic (S:D) ratios were elevated (>95th percentile for gestational age [GA]). The term protocol (March 2010–July 2012) specified delivery at 390/7 weeks with normal S:D ratios and 370/7 weeks with elevated S:D ratios when antenatal testing was reassuring.Results There were 228 and 312 women in the early term and term protocol, respectively, who met inclusion criteria. Compared with the early term group, the term group had an increased median GA at delivery (37.1 vs. 38.6%, p < 0.001), decreased deliveries less than 370/7 weeks (37 vs. 24%, p = 0.01) and decreased neonatal intensive care unit (NICU) admissions (38 vs. 28%, p = 0.02).Conclusion A protocol specifying delivery at 390/7 weeks when UA S:D ratios are normal and delivery at 370/7 weeks when UA S:D ratios are elevated when other antenatal testing is reassuring in FGR: (1) prolonged gestation, (2) decreased preterm births, and (3) decreased NICU admissions.
Keywords: fetal growth restriction; intrauterine growth restriction; management; surveillance